2014
DOI: 10.1126/science.1248523
|View full text |Cite
|
Sign up to set email alerts
|

Optical Control of Muscle Function by Transplantation of Stem Cell–Derived Motor Neurons in Mice

Abstract: Damage to the central nervous system caused by traumatic injury or neurological disorders can lead to permanent loss of voluntary motor function and muscle paralysis. Here, we describe an approach that circumvents central motor circuit pathology to restore specific skeletal muscle function. We generated murine embryonic stem cell-derived motor neurons that express the light-sensitive ion channel channelrhodopsin-2, which we then engrafted into partially denervated branches of the sciatic nerve of adult mice. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
152
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(175 citation statements)
references
References 27 publications
8
152
1
Order By: Relevance
“…Importantly, this study also demonstrated that motor units activated by optical stimulation are recruited in normal physiological order, with smaller, fatigue-resistant motor units being recruited at lower optical stimulus intensities and larger fatigable motor units only being activated at higher intensities [26]. The same physiological recruitment of ChR2 expressing motor units and prevention of muscle fatigue was also verified in our recent study [3], discussed below. Theoretical modelling of the orderly recruitment of motor units in peripheral optogenetic neural stimulation (PONS) suggests that the reduced internodal distance in small diameter myelinated motor axons is an essential parameter underlying this phenomenon [27].…”
Section: Artificial Control Of Motor Neuron Function: Optical Stimulasupporting
confidence: 78%
See 3 more Smart Citations
“…Importantly, this study also demonstrated that motor units activated by optical stimulation are recruited in normal physiological order, with smaller, fatigue-resistant motor units being recruited at lower optical stimulus intensities and larger fatigable motor units only being activated at higher intensities [26]. The same physiological recruitment of ChR2 expressing motor units and prevention of muscle fatigue was also verified in our recent study [3], discussed below. Theoretical modelling of the orderly recruitment of motor units in peripheral optogenetic neural stimulation (PONS) suggests that the reduced internodal distance in small diameter myelinated motor axons is an essential parameter underlying this phenomenon [27].…”
Section: Artificial Control Of Motor Neuron Function: Optical Stimulasupporting
confidence: 78%
“…Strategies targeting the peripheral rather than central nervous system [19] may circumvent the challenges described above and this approach has been used to restore specific motor functions in animal models [3].…”
Section: Stem Cell-based Therapeutic Strategies Targeting Peripheralmentioning
confidence: 99%
See 2 more Smart Citations
“…Optogenetics thus allows for the noninvasive activation or inhibition of specific cells with light, a method that can be leveraged to combat a wide range of neurological conditions. Already, the potential of optogenetic techniques has been demonstrated in sciatic nerve injury [2], Parkinson's disease [3], epilepsy [4], depression [5,6], and retinal degeneration [7,8]. In this work, we describe a new method of using optogenetic techniques to study retinal circuit interactions between neurons and vascular cells, and show how this general approach can be potentially applied to treat neurological diseases.…”
Section: Introductionmentioning
confidence: 99%